Aplikasi Pencatatan Kehadiran Pegawai PT. Tri Difta Lubrindo - Muhammad Hafizh Ariansyah (UNIVERSITAS KALBIS, 2022)
The attendance or attendance recording system has an important role in every company where attendance is one of the main supports that can support and motivate every activity carried out in it. Like the attendance recording system at PT. Tri Difta Lubrindo who still uses the manual attendance system (signature). This method is very vulnerable for companies because of the uncontrollable level of discipline. can be abused by irresponsible and ineffective people. This allows employee data to be lost and makes it difficult to recapitulate employee attendance data because it takes a lot of time and effort. The purpose of this research is to design a computer-based employee attendance recording system using fingerprint media at PT. Tri Difta Lubrindo. The method used in this research is observation to PT. Tri Difta Lubrindo, interviews with HRD and using the prototyping method as a system development method and using black box testing as a system testing method. The result of this research is an employee attendance recording system at PT. Tri Difta Lubrindo